Targeting the Intellectuals: Advertising and Propaganda for the Lampung Colonization Program in Newspapers (1930–1941) - Kurohman, M. Taofik; Wargadalem, Farida R.; Pahlevi, M. Reza; Fernanda, Tyas (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2026)
This study investigates the Dutch East Indies government's strategic promotion of “colonization”—a state-managed migration program aimed at relocating populations from densely populated Java to Lampung between 1930 and 1941. This era marks the third and peak phase of the program, characterized by both policy shifts and a significant surge in participation. Employing historical methods and archival discourse analysis, the research examines a corpus of newspapers published within this timeframe. Findings reveal a strategic alignment between colonial recruitment strategies and pro-migration narratives specifically designed to target the educated “intellectual” class. Unlike traditional methods, the government utilized sophisticated propaganda strategically embedded within news columns to project an appearance of objectivity and bypass the critical defenses of literate readers. This study contributes a nuanced perspective to the historiography of colonial migration and press history, illustrating how media discourse was engineered as a sophisticated recruitment tool during a period of global economic depression.